Cerita lipur lara terpilih berdasarkan pendekatan pengurusan / Mohamad Zuber Ismail - Mohamad Zuber , Ismail (2017)
This study presents an assessment of a new approach in the world of Malay literature as cross-disciplinary in nature. It attempts to examine an aspect of modern management contained in Hikayat Anggun Cik Tunggal (1985), Hikayat Awang Sulung Merah Muda. (1988), Hikayat Malim Deman (1998), Hikayat Malim Dewa (1998) and Hikayat Raja Muda (1998). In doing literary criticism, there are various approaches that have been used by critics. In this study, discussions were based on Management Approach which has been highlighted by Mohamad Mokhtar Abu Hassan through a series of working papers that were presented at the Himpunan Ilmuwan Sasterawan Melayu, Universiti Perguruan Sultan Idris, (UPSI) in 2013. This management approach has been reinforced in the Lecture prime organized by the Department of Arts, Academy of Malay Studies, Universiti Malaya on August 4, 2016. The texts were discussed in detail to achieve three main objectives, namely to identify management principles contained in the folklore story was selected. Second, analyse the folklore story was based on the principles applied in the management approach. Third, formulate effective management aspects in the folklore story was selected. With the proposed definition of the concept of management as well as management principles, management approach has been used as an indicator to analyse and discuss the management principles contained in the soap opera's story. Five principles in the approach that is the backbone of the study, namely the principles of planning, leadership principles, the principle of organizing, staffing principle and the principle of control. The study found several findings stems from the analysis using management approach. The findings prove that the soap opera story Malay bump a high tendency to highlight the five principles of management stems from an analysis of the structure of the work. Restoration management principles in the work of this prolific scientists managed to exude power and intellectual acumen author thought, especially in raising aspects of management in this traditional work. This study proves that the management aspect is an important mechanism raised in literary criticism, criticism not only make the world more interesting and challenging, even to educate and enlighten audiences that the importance of management in building society. Management approach put forward in the world of literary criticism is expected to benefit and contribution as well as opening up a new dimension in the sheet and the world's research literature homeland. Exploration results using the model of management which approach is expected to provide benefit and open a sheet and a new dimension in the world of literary criticism in Malaysia.